The impact of the events on the improvement of community economy in the waterfront area sambas - Evita, Rossi; Rosalina, Tita (Institut Pariwisata dan Bisnis Internasional, 2021)
Tourism activities in Indonesia are currently the focus of attention of the central and regional governments as one of the sectors that play a very important role in the regional development. Seeing the development of tourism trends in recent years, the local government, especially the Disparpora of Sambas Regency continues to carry out various programs to improve tourism performance, among others by organizing the Bidar Sampan Competition that is held annually and becomes a national cultural event. This study used a quantitative descriptive method. Data were collected through questionnaires and interviews. The results of the questionnaire were analyzed using SPSS 20. The variable of tourism event has no effect and is not significant for improving the community’s economy. This can be seen from the significant of 0.122, which is greater than the significance level (0.05). The tcount was 1.595, is smaller than the ttable (2.04841), with the regression coefficient of 0.446. Tourism events impact on people’s income. Before the tourism was held, the community’s income level was relatively moderate. After the tourism event, people’s income has increased, while after the event, the income of the community returned to normal.